2006
DOI: 10.1111/j.1572-0241.2006.00456.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Immune Responses Predict Rapid Disease Progression among Children with Crohn's Disease: Immune Responses Predict Disease Progression

Abstract: The presence and magnitude of immune responses to microbial antigens are significantly associated with more aggressive disease phenotypes among children with CD. This is the first study to prospectively demonstrate that the time to develop a disease complication in children is significantly faster in the presence of immune reactivity, thereby predicting disease progression to more aggressive disease phenotypes among pediatric CD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
172
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(182 citation statements)
references
References 24 publications
6
172
0
4
Order By: Relevance
“…27 It is possible that the colon is a major site of the flagellin-specific IgG production since its highest density of microbes in the body. The produced IgG may be partially absorbed into the blood stream and detected in the serum as reported, 27,28 and partially bound to immune cells, such as mast cells, in local tissue as shown by the present study.…”
Section: Discussionmentioning
confidence: 69%
“…27 It is possible that the colon is a major site of the flagellin-specific IgG production since its highest density of microbes in the body. The produced IgG may be partially absorbed into the blood stream and detected in the serum as reported, 27,28 and partially bound to immune cells, such as mast cells, in local tissue as shown by the present study.…”
Section: Discussionmentioning
confidence: 69%
“…The evolution of ser um immune response from diagnostic markers to markers of disease behavior and perhaps prognostic information has resulted in studies that have shown that the presence and magnitude of immune responses in a given child is associated with more aggressive disease phenotypes and more rapid disease progression to complication and surgery. Larger scale studies are underway to confirm these preliminary findings and to further develop a risk assessment tool to identify children at risk of more aggressive disease and subsequent introduction of early intervention [11,12] .…”
Section: Etiopathogenesismentioning
confidence: 99%
“…More recently, two commercially available panels of antibodies to microbial antigens have been associated with complicated small bowel disease behavior in adult and pediatric CD in cross-sectional and prospective studies. [19][20][21][22][23][24] These panels include antibodies directed at several microbial antigens including oligomannan (anti-Saccharomyces cerevisiae or ASCA), Escherichia coli outer membrane porin C (anti-OmpC), flagellin (anti-CBir1), antilaminaribioside (ALCA), antimannobioside (AMCA), antichitobioside (ACCA), antichitin (anti-C), and antilaminarin (anti-L). 21,[25][26][27][28][29][30] The clinical utility of these panels is an area of ongoing interest, but their greatest potential may lie in their predictive capacity (for a more detailed review see the article by Rubin in this issue).…”
Section: The Challenge Of Choosing the Appropriate Therapy For The Nementioning
confidence: 99%